Antioxidative Defense System, Hormones, and Metabolite Accumulation in Different Plant Parts of Two Contrasting Rice Cultivars as Influenced by Plant Growth Regulators Under Heat Stress - Al-Zahrani, Hassan S.; Alharby, Hesham F.; Fahad, Shah (Frontiers in Plant Science, 2022)
We examined the metobloic, hormonal, enzymatic and non-enzymatic responses of various plant components (leaf, root and xylem sap) to plant growth regulators [methyl jasmonates (MeJA); ascorbic acid (Vc); brassinosteroids (Br); triazoles (Tr); alpha-tocopherol (Ve) and control] under heat stress [ambient temperature (AT), heat stress at night time(HNT) and high stress at day (HDT)] in heat sensitive (IR-64) and tolerant (Huanghuazhan) rice cultivars under greenhouse condition. Heat stress altered the antioxidant activities and hormonal balance, and rigorously reduced total soluble sugars, proteins, and proline, while increased H2O2 and MDA accumulation in the plant xylem sap and leaves of both tested cultivars but the their impact was more pronounced in IR-64. The SOD, POD, CAT, APX, GR, GSH, DHAR, and MDHAR activities were comparatively higher in Huanghuazhan than IR-64 in response to temperature stress when compared to AT. Heat stress increased ABA levels in both rice cultivars especially in IR-64. The highest concentrations of hormones were recorded in roots followed by leaf and xylem sap in both cultivars. The HDT and HNT stresses severely reduced the concentrations of all cytokinin types (except iP9G and tZ9G), and IAA in different plant parts of rice cultivars. The HNT was more detrimental for hormones and metabolites synthesis in both cultivars. The growth regulators especially Vc+Br+Ve+MeJA were comparatively more effective in minimizing the hostile impact of heat stress in most of the studied traits and shall be applied for obtaining optimum yield of rice in subtropical and tropical areas under changing climatic conditions.